Case report: Severe pneumonia and pneumomediastinum in a previously robust adolescent caused by Omicron BA.5.2 - Xiang, Tianxin; Fang, Jianhua; Cheng, Tao; Li, Zhongmin; Wu, Daxian; Zhang, Shouhua; Ge, Shanfei; Zhang, Wei (Frontiers in Medicine, 2023)
Severe pneumonia is occasional and mediastinal emphysema is rare in COVID-19 patients, especially for those who infected with Omicron. In addition, whether severe pneumonia or mediastinal emphysema often occurs in patients with older age, poor physical condition, or underlying diseases. So far, severe pneumonia and mediastinal emphysema due to Omicron infection was not reported in a previously young person with excellent physical condition. Here, we reported such a case with above manifestations in a robust adolescent infected with Omicron BA.5.2.